The challenge of following a research line within the framework of student scientific production - Guillen LeÃ³n, Laura Adalys; VitÃ³n Castillo, AdriÃ¡n Alejandro (Revista de Ciencias Médicas de Pinar del Río, 2022)
The challenge of following a research line within the framework of student scientific production